Permainan Tradisional Boy-Boyan: Upaya Peningkatan Kemampuan Mengenal Angka dalam Bahasa Madura - A’yun, Qurrotu; Nurhayati, Nurhayati; Damayanti, Nadifa Alfani; Nadhifah, Ainun; Fadilah, Nur Utami; Nazarullail, Fikri (Nak-Kanak: Journal of Child Research, 2024)
The study aims to determine the development of number recognition skills in Madurese language for children aged 5-6 years and to assess the percentage improvement in number recognition skills in Madurese among Group B children at Tanjung Jati Kindergarten through the traditional game "boy-boyan" during the 2022/2023 academic year. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model. The classroom action research was conducted in four cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects and data sources for this study were Group B children at Tanjung Jati Kindergarten, totaling 9 children, consisting of 3 boys and 6 girls. Data collection techniques in this study included observation and documentation. The data analysis techniques used were qualitative and quantitative analysis. The results of the classroom action research show an improvement in the children's ability to recognize numbers in Madurese at each stage. This can be seen from the pre-cycle results, where the children's speaking ability was generally in the "Starting to Develop" category at 38.95%. No children had reached the "Developing as Expected" or "Developing Very Well" categories. However, after the learning process through the traditional game of "boy-boyan," there was an increase in speaking skills. In cycle 1, the children's speaking ability reached the "Developing as Expected" category at 70.4%. In cycle 2, their speaking ability reached the "Developing Very Well" category at 88.9%. Based on the results of this classroom action research, the teacher was able to improve the children's ability to recognize numbers in Madurese in Group B at Tanjung Jati Kindergarten through the traditional game "boy-boyan."